Graphene oxide and Ag engulfed TiO2 nanotube arrays for enhanced electron mobility and visible-light-driven photocatalytic performance - Sim, L.C.; Leong, K.H.; Ibrahim, S.; Saravanan, P. (Royal Society of Chemistry, 2014)
The visible-light-driven photocatalytic degradation of Methylene Blue (MB) and 2-chlorophenol (2-CP) were investigated using the composite of Ag nanoparticles (Ag NPs) and graphene oxide (GO) deposited over TiO2 nanotube arrays (TNTs). The resulting TNTs in the composite showed 100% anatase phase with no occurrence of the rutile phase. An implicit microscopic and spectroscopic technique (FESEM, HRTEM, FTIR and Raman analysis) confirmed the presence of Ag NPs and GO in the composite photocatalyst. It also exhibited an evident shift of the absorption edge in the visible range. The successful depositions of Ag contributed to improved photocatalytic activity in the visible spectrum owing to the existence of localized surface plasmon resonance (LSPR), and further the deposition of GO minimized the recombination of electron–hole pairs. The photocatalytic degradation of both MB and 2-CP followed pseudo-second order kinetics. In the primary run, both MB and 2-CP exhibited almost similar degradation efficiency of 68.3 and 66.8%, respectively. The reusability studies showed a deprived performance for MB degradation than that of 2-CP, due to chemisorption of MB. The prepared composite exhibited significantly larger enhancement in the photocatalytic oxidation of pollutants with greater electrons mobility to reactive sites of GO and Ag.